BCPT: Participant Update - K. Smigel (JNCI Journal of the National Cancer Institute, 1994)
CCL19 and CCL21 interact differentially with their shared receptor CCR7. A key amino acid important for CCL19-mediated receptor activation is arginine 209 (R209) in extracellular loop 2 (ECL2) of CCR7. CCL21 activation of CCR7, in contrast, does not depend on R209. Using chimeric versions of CCL19 and CCL21, we investigate the importance of the N-terminal region, core domain and C-terminal region of CCL19 and CCL21 in contributing to this distinction. Overall, signalling via Gαi and β-arrestin2 recruitment induced by CCL19 and all variants containing the N-terminal region of CCL19 is negatively impacted by substituting arginine 209 with an alanine (R209A), whereas signalling induced by ligands with the N-terminal region of CCL21 is either unaffected or positively affected by this substitution. Of interest, the R209A substitution greatly improves the ability of CCL21 and all chemokine variants carrying the N-terminal region of CCL21 to induce β-arrestin2 recruitment by CCR7, with a general two-fold increase in efficacy at 100-nM chemokine concentrations. Our data fit with the proposed model for CCL19 and CCL21 docking at CCR7, where the more negatively charged N-terminus of CCL19 contacts R209 during insertion into the CCR7 binding pocket, while CCL21 contacts the binding pocket in a different manner.